"Walk in Grace": A Kitchen-Table Talk on Cultivating Care, Dignity, Love, and Respect in Education. Issue 3 (3rd July 2021) - Lala, Erika; Bhattacharya, Kakali; Nieto, Sonia; Vilson, José Luis
ABSTRACT: Grounded in the power of our interconnectedness and humanity, this kitchen-table talk explores what it means to cultivate care, dignity, love, and respect in education. We begin by sharing personal offerings and stories that center us in this conversation, and these lead us to exploring the possibilities in showing care and feeling cared for in education spaces. We name the vitality and urgency of this work and discuss the impact of collaborating with others as we push forward. Recognizing a variety of challenges that serve to hinder our efforts, we close by reviewing what keeps us going and offering some advice to those unsure of their next opportunity for impact.